2019
DOI: 10.2139/ssrn.3319088
|View full text |Cite
|
Sign up to set email alerts
|

Nudging with Care: The Risks and Benefits of Social Information

Abstract: Norms and nudges are both popular types of interventions. Recent years have seen the rise of 'norm-nudges'-nudges whose mechanism of action relies on social norms, eliciting or changing social expectations. Norm-nudges can be powerful interventions, but they can easily fail to be effective and can even backfire unless they are designed with care. We highlight important considerations when designing norm-nudges and discuss a general model of social behavior based on expectations and conditional preferences. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
131
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 93 publications
(140 citation statements)
references
References 57 publications
4
131
0
5
Order By: Relevance
“…Norm messages varied along two dimensions: content and framing. With respect to the content, we followed the tradition of norm-nudge interventions (see conceptual discussion in Bicchieri and Dimant, 2019). We also followed the social norm tradition of Bicchieri (2006, see also Cialdini and Trost, 1998;Cialdini et al, 2006;Schultz et al, 2007) by distinguishing between empirical information (what the majority of other people have done in a similar situation) and normative information (what the majority of other people have approved of doing in a similar situation).…”
Section: Part 1: Norm-nudgementioning
confidence: 99%
See 4 more Smart Citations
“…Norm messages varied along two dimensions: content and framing. With respect to the content, we followed the tradition of norm-nudge interventions (see conceptual discussion in Bicchieri and Dimant, 2019). We also followed the social norm tradition of Bicchieri (2006, see also Cialdini and Trost, 1998;Cialdini et al, 2006;Schultz et al, 2007) by distinguishing between empirical information (what the majority of other people have done in a similar situation) and normative information (what the majority of other people have approved of doing in a similar situation).…”
Section: Part 1: Norm-nudgementioning
confidence: 99%
“…Prior research has shown that providing "norm-nudges", such as information on how relevant peers behave and what behavior they consider appropriate, can crucially affect whether individuals adhere to norms and, in turn, demonstrate behavioral change (Bicchieri and Dimant, 2019). Our paper seeks to understand how different versions of truthful normrelated information and their frames (positive versus negative) affect deviant behavior in the form of misreporting a random outcome for a monetary bonus.…”
Section: Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations